CXCL10 conditions alveolar macrophages within the premetastatic niche to promote metastasis. (1st July 2022) - Shang, Chao; Sun, Yingying; Wang, Yawei; Shi, Huifang; Han, Xiaoqing; Mo, Yan; Wang, Dake; Ke, Yueshuang; Zeng, Xianlu
Abstract: Formation of the premetastatic niche is triggered by primary tumors and contributes to cancer metastasis. Evidence indicating the roles of macrophages in metastatic niche formation and organ-specific metastatic tropism has been steadily accumulating. However, the role of tissue-resident macrophages in the establishment of the premetastatic niche is not clearly defined. Here, we report that alveolar macrophages (AMs), which are lung tissue-resident macrophages, play a critical role in initiating the recruitment of monocytic myeloid-derived suppressor cells (mo-MDSCs) and the subsequent premetastatic niche formation by increasing CCL12 expression. We found that CXCL10 can induce CCL12 expression by activating CXCR3 and TLR4 in AMs. CXCR3/TLR4 deficiency or inhibition of its activity reduces CCL12 expression in AMs and subsequent mo-MDSC recruitment to the premetastatic niche, thereby attenuating lung metastasis. In addition, Ube2o is a negative modulator of CXCL10-induced CCL12 expression. Downregulation of Ube2o in AMs under tumor conditions enhances TAK1-NF-κB/ERK/JNK signaling and CXCL10-induced CCL12 expression by promoting TRAF6 polyubiquitination and inhibiting DDX3X degradation. Targeting mo-MDSC recruitment via the CXCL10-CXCR3/TLR4-CCL12 axis in AMs may have therapeutic potential for suppressing lung metastasis. Highlights: AMs promote the formation of premetastatic niche by recruiting mo-MDSCs. Increased CCL12 in AMs leads to mo-MDSC recruitment. CXCL10 is required for induction of CCL12 expression in AMs. The CXCL10-CXCR3/TLR4 axis is essential for induction of CCL12 expression in AMs. Downregulation of Ube2o enhances CXCL10-induced CCL12 expression in AMs.